Pengaruh Kualitas Layanan dan Keunggulan Kompetitif Terhadap Kepuasan Pelanggan yang Berdampak pada Loyalitas Pelanggan Soto Mie Bogor Bang Alex - Mita Andriani; Ika Suhartanti Darmo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This research aims for the effect of Service Quality and Competitive Advantage on Customer Satisfaction that impacts on Customer Loyalty. Data processing in this study uses quantitative methods. The hypothesis testing method using the t test method and linear regression test. The results showed that service quality has a significant effect on customer satisfaction, competitive advantage has a significant effect on customer satisfaction, service quality and competitive advantage together have a significant effect on customer satisfaction, and customer satisfaction has a significant effect on customer loyalty.